The role of Diffusion-Weighted Imaging in better delineating the extent of Diffuse Axonal Injury in a pediatric patient: A case report and brief review of the literature - Solomou, Aikaterini; Kraniotis, Pantelis; Patriarcheas, Vasileios (Archives of Case Reports, 2020)
Introduction: Diffuse axonal injury (DAI) is a major cause of disability in the pediatric patient. Herein we describe the MRI/DWI findings in a case with DAI. We also discuss the current role of CT and MRI with DWI in the evaluation of DAI. Aim of the study: To stress the role of diffusion-weighted imaging in diffuse axonal injury. Methods: A pediatric patient, who was hospitalized in the ICU, was submitted to MRI with DWI for the evaluation of brain lesions. The patient was scanned with T1-weighted images, T2-weighted images, FLAIR, T2*-weighted images and diffusion weighted images. Result: Brain lesions caused by DAI were more conspicuous on diffusion-weighted images compared to FLAIR images. T2*-weighted images were a helpful adjunct in showing micro-hemorrhages. Conclusion: T2*-weighted images and FLAIR images alone underestimate the true extent brain lesions in DAI compared to DWI.